Exploring Ionic Liquid-Based Liquid–Liquid Extraction as a Benign Alternative for Sustainable Wastewater Treatment - Padinhattath, Sachind Prabha; Shaibuna, M.; Gardas, Ramesh L. (Sustainability & Circularity NOW, 2025)
The uncontrolled release of industrial effluents containing micropollutants (MPs), dyes, and heavy metal ions contaminates natural water bodies posing threats to health and the environment. Conventional treatment methods often struggle with challenges such as prolonged processing time, low specificity, and risk of producing secondary pollutants. Liquid–liquid extraction (LLE) technique utilizing ionic liquids (ILs) has emerged as a viable alternative for the elimination of contaminants from wastewater. ILs, characterized by minimal volatility and tunable physicochemical properties, facilitate the precise elimination of contaminants from industrial effluent. IL-LLE streamlines the experimental setup, lowers energy consumption, promotes recyclability for reuse, enhances mechanistic understanding, and hence provides a sustainable alternative to industrial effluent treatment. This review provides a comprehensive analysis of IL-LLE approaches for wastewater treatment, commencing with an overview of the historical evolution of ILs, tracing their progression from initial research to contemporary and advanced applications. The article primarily examines the practical applications of IL-LLE, demonstrating how these approaches are employed to efficiently remove diverse contaminants from both simulated and actual industrial wastewater samples. As a whole, the review consolidates the versatility and efficiency of IL-based LLE in addressing various challenges in wastewater treatment.
Keywords: Ionic liquid; Wastewater; Liquid–liquid extraction; Micropollutants; Dyes; Heavy metals; Reuse